Understanding how qualifying-year accounting students construe potential employers when making employer-choice decisions - Sher, Jordan (Organisational Psychology, 2021)
This study explores how Postgraduate Diploma of Accounting (PGDA) students at the University of Cape Town consider potential employers when making employer-choice decisions. Kelly's Repertory Grid technique was employed during structured interviews with twelve (N = 12) PGDA students. Perceptions about potential accounting employers varied across the participants. Investec and Nedbank, both of which are Banks, were construed similarly for 11 out of 12 participants. On average, three of the Big Four auditing firms were mostly construed similarly, namely EY, PwC and Deloitte, with KPMG construed differently by the majority of participants. Nolands and Mazars were construed similarly for 8 participants. Transnet was perceived distinctly from the other firms by most participants. The most frequently elicited constructs were regarding progression opportunities, international exposure and ethical reputation. The following themes emerged from a thematic analysis of the participants' interview responses: (1) organizational attractiveness, (2) exposure gained during training, (3) work environment, (4) progression opportunities, (5) diversity policies, (6) brand awareness, (7) workplace flexibility and work-life balance, (8) the recruitment process, (9) corporate social responsibility, and (10) a felt moral responsibility to the employer. This study proposes that by understanding how students construe and perceive different sets of potential accounting employers, employers could improve their attraction and retention strategies. The findings of this study could also be of benefit to career counsellors and others tasked with advising and guiding accounting graduates.